Factor: x2 + 3x + 7x + 21

x^2 + 3x + 7x + 21 = x^2 + 10x + 21 = (x+7)(x+3)

Question

Asked 6/28/2012 7:52:16 PM

Updated 6/22/2014 2:51:42 PM

1 Answer/Comment

Flagged by andrewpallarca [6/22/2014 2:51:42 PM]

Rating

3

x^2 + 3x + 7x + 21 = x^2 + 10x + 21 = (x+7)(x+3)

Added 7/1/2012 2:42:48 AM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/22/2014 2:51:40 PM], Rated good by jeifunk

Factor: x2 – 1 **Weegy:** x ² - 1 = (x - 1) (x + 1)
Check
(x - 1) (x + 1)
x (x + 1) - 1 (x + 1)
x ² + x - x - 1
x ² - 1 (More)

Question

Expert Answered

Updated 6/22/2014 2:51:59 PM

0 Answers/Comments

Factor: x2 – 1 **Weegy:** wait 2 min I will be right back with the ans. (More)

Question

Updated 6/20/2014 6:10:50 PM

1 Answer/Comment

x^2 – 1 = (x + 1)(x - 1)

Added 6/20/2014 6:10:32 PM

This answer has been added to the Weegy Knowledgebase

Factor: 4x2 – 81y2 **Weegy:** 4x² - 81y² = 0
4x² = 81y²
x² = 81/4y²
x = ± 9/2y
= x - 9/2y, = 2x - 9y
= x + 9/2y, = 2x + 9y
Answer: (2x - 9y)(2x + 9y) (More)

Question

Expert Answered

Updated 6/22/2014 2:52:31 PM

0 Answers/Comments

Factor: x2 – 11x + 18 **Weegy:** quadratic equation (More)

Question

Updated 7/14/2014 7:51:07 PM

1 Answer/Comment

x^2 – 11x + 18 = (x - 9)(x - 2)

Added 7/14/2014 7:51:05 PM

This answer has been added to the Weegy Knowledgebase

Factor: x2 – 11x + 18 **Weegy:** quadratic equation (More)

Question

Updated 6/20/2014 6:13:23 PM

1 Answer/Comment

x^2 – 11x + 18 = (x - 2)(x - 9)

Added 6/20/2014 6:13:21 PM

This answer has been confirmed as correct, not copied, and helpful.

Confirmed by andrewpallarca [6/21/2014 1:46:17 AM]

22,436,362 questions answered

There are no comments.